Pengembangan Bahan Ajar untuk Menunjang Pembelajaran Kurikulum Merdeka pada Materi Laju Reaksi Fase F SMA/MA - Hamsil, Fatia; Mawardi, Mawardi; Suryani, Okta (Universitas Nusantara PGRI Kediri, 2024)
This aim of this research is to achieve the following about development teaching resources equipped with chemical multiple representations on reaction rate material that support independent curiculum learning in building students’ mental models phase F SMA/MA. Educational research design or (EDR) is a type of research used with Plomp’s development method, which is a systematic method for designing and evaluating educational programs. Three lecturers in chemistry, two teachers who teach chemistry and nine students became the subject of this study. Data were gathered by two questionnaire, one for validation and other for practicality. The resulting data demonstrated that exhibited the average the construct validity (0.94) with category thas is valid. Moreover, the practicality test exhibited a 97% teacher practicality rate and an average student practically rate of 93% revealed with very practical. So, the concluding remarks of this study that the teaching materials developed on reaction rate material to support independent curriculum learning equipped with chemical multirepresentation are both valid and highly practical.